Análise da resistência a sistemas de informação: a percepção dos gestores de tecnologia da informação acerca de sistemas ERP - Gaete, Luciano (2010)
The main goal of this work is to obtain and empirically validate an Information System Resistance model which could be applied to better understand the resistance phenomenon to information systems. The study was conducted by an explanatory research in a quantitative approach, based on an extensive review of the pertinent world literature that resulted in the consolidation of the main existing theories and models about the subject. In the proposed model a set of aspects was considered that although already having been discussed in the available literature, in its majority has not yet been empirically tested, which are: (i) the idiosyncratic individual characteristics, (ii) the technical aspects of the information systems, (iii) the socio-technical interaction aspects, (iv) the power and political interaction aspects and finally, (v) the organization context in which technology and man are inserted and interact. Then a meta-model was done as well as a survey. Once applied on Internet, the survey obtained 169 valid responses, from Brazilian IT managers who had experienced at least one experience with ERPs - Enterprise Resource Planning Systems – implementation. To obtain the final model statistical factorial analysis was applied to the answers. Each identified factor in the model corresponds to an expected cause to the information system resistance behavior. The model was than submitted to hypotheses tests trying to establish the relation between each resultant factor and the direct resistance perception of each respondent. A consolidated information system resistance model based on the Brazilian IT Managers perception about the ERPs implementation has emerged from this study.